Empirical study of accessibility tools: A proposal for the inclusion of people with disability (Revista Direito em Debate, 2024)
Access to education is a basic right for every person, but neglected for people with disability (PWD). As a tool to qualify individuals the labor market, access to education is essential for the insertion of any subject in society. The objective here is to verify whether the university environment, as a training space for qualified professionals, is prepared to receive PWD. We carried out a comparative study between the existing inclusive actions in business schools with an institutional relationship. We collected and analyzed data on the institutional websites of international business schools and a Brazilian one, once the right to information is guaranteed in the International Convention. Each university presents policies suited to its community and none of them has an ideal model to be followed. Analyzes indicate that, as a rule, the university environment (both in Brazil and in international partnerships) is not prepared to welcome PWDs. A document centralizing the accessibility policies and their adequate dissemination are important so that the PWD knows the type of reception that they can expect and demand from that organization. Beyond fulfilling the legal requirements, environmental and political adequacy create accessible places that benefit the whole community in addition to the people with disability.
Keywords: education; university; accessibility; professional training; people with disability (PCD)